A high-voltage sodium-ion battery positive electrode material and preparation method

By doping and strengthening the cathode material of sodium ion battery, Ca2+, Al3+, Mg2+, and in-situ coated with borate and La elements, the problem of poor capacity attenuation and poor circulation performance of the material at high voltage is solved, and higher capacity and circulation stability are achieved.

CN119361665BActive Publication Date: 2025-04-08JIANGMEN KANHOO IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411932603.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Existing sodium ion battery positive electrode materials have problems with capacity attenuation and poor circulation performance in high voltage application scenarios.

Method used

By performing Ca2+ doping reinforcement on the alkali metal layer, Al3+ doping reinforcement on the transition metal layer, and using Mg2+ to increase the material conductivity, and finally the material is coated in situ. The coating material contains borate and La elements to improve the material's high-voltage resistance and surface stability.

Benefits of technology

The capacity and cycling performance of the sodium ion battery positive electrode material under high voltage conditions is significantly improved, and the material's high voltage resistance and surface stability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361665B_ABST
    Figure CN119361665B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of sodium ion batteries and discloses a high-voltage resistant sodium ion battery positive electrode material, comprising a core layer and a coating layer; the chemical formula of the core layer is Na x Ca y (NiFeMn) 0.33x(1‑z‑e) Al z Mg e O2; the chemical formula of the coating layer is Na3La2(BO3)3·(AF m ) n; 0.99≤x+y≤1.04, 0.01≤y≤0.05, 0.01≤z≤0.1, 0≤n≤0.05, 0.0023≤e≤0.023; A is Ca and / or Al, and m is the valence state of element A. The positive electrode material realizes the interface stability of the core layer material, the coating material, and the core layer material and the coating material through core layer doping and coating, especially significantly improves the surface stability of the doped core layer, and improves the capacity and cycle performance under high voltage conditions. At the same time, the present invention also provides a preparation method of the high-voltage resistant sodium ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a high-voltage resistant sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Conventional O3 sodium-ion battery positive electrode materials can only be used at 3.9-4.0V. Due to the special arrangement of ions in the O3 material, sodium ions occupy the octahedral position. When applied at a higher voltage of 4.1V or above, a large number of sodium ions are released, and the transition metal layer in the structure slips in order to maintain structural stability, and the hexagonal P3 phase is distorted into a monoclinic P'3 phase. At this time, the structural reversibility deteriorates, and the material exposes slip surface defects, which intensifies the reaction with the electrolyte, resulting in problems such as capacity decay and gas production.

[0003] The technical problem to be solved in this case is: how to improve the capacity and cycle performance of sodium-ion battery positive electrode materials in high-voltage application scenarios. Summary of the invention

[0004] The object of the present invention is to provide a positive electrode material for a high-voltage sodium-ion battery. 2+ Doping reinforcement, Al 3+ Doping reinforcement, then, using Mg 2+ Increase material conductivity and reduce Al doping 3+ The polarization brought about is finally coated in situ on the material. The coating material contains borate and La elements, which on the one hand isolate the corrosion of the electrolyte to the material, thereby improving the material's ability to withstand high voltage. On the other hand, the high-strength boron-oxygen bond of borate is used for shallow doping to improve the stability of the surface layer. The La element is used as the main body of the coating layer framework to improve the conductivity of the coating layer. La has a high-strength bond energy to maintain the stability of the coating layer structure, thereby ultimately achieving the stability of the core layer material, the coating material, and the interface between the core layer material and the coating material, especially the significant improvement of the surface stability of the doped core layer, thereby improving the capacity and cycle performance under high voltage conditions.

[0005] At the same time, the present invention also provides a method for preparing the high-voltage resistant sodium ion battery positive electrode material.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A high-voltage sodium-ion battery positive electrode material, comprising a core layer and a coating layer;

[0008] The chemical formula of the core layer is Na x Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg eO2; the chemical formula of the coating layer is Na3La2(BO3)3·(AF m ) n ;

[0009] 0.99≤x+2y≤1.04, 0.01≤y≤0.05, 0.01≤z≤0.1, 0≤n≤0.05, 0.0023≤e≤0.023; A is Na, Mg and / or Al, and m is the valence state of the A element.

[0010] The present invention is to carry out Ca treatment on the alkali metal layer. 2+ Doping reinforcement, Al 3+ Doping reinforcement, then, using Mg 2+ Increase material conductivity and reduce Al doping 3+ The polarization brought about is finally carried out on the material by in-situ coating. The coating material contains borate and La elements, which on the one hand isolate the corrosion of the material by the electrolyte, thereby improving the material's ability to withstand high voltage. On the other hand, the high-strength boron-oxygen bond of borate is used for shallow doping to improve the stability of the surface layer, and the high-strength bond energy of La element is used to maintain the stability of the coating layer structure, thereby ultimately achieving the stability of the core layer material, the coating material, and the interface between the core layer material and the coating material, especially the significant improvement of the surface stability of the doped core layer, thereby improving the capacity and cycle performance under high voltage conditions.

[0011] In the present invention, the fluoride of the coating layer is an optional material. During the experiment, it was screened that sodium fluoride, magnesium fluoride, aluminum fluoride and other materials can improve the performance of the positive electrode material after being added to the coating material, which can improve at least one of the 0.1C charge gram capacity, 0.1C discharge gram capacity, 1C discharge gram capacity, and 50 weeks of 1C cycle. We believe that its mechanism is: through the coating of fluoride and the doping of the shallow layer, the structural stability of the material and the shallow layer is further optimized, and then through the optimization of metal elements, performance improvements in multiple aspects are achieved.

[0012] In the above-mentioned high-voltage-resistant sodium-ion battery positive electrode material, the weight of the coating layer is equivalent to 0.8-2% of the weight of the core layer.

[0013] At the same time, the present invention also discloses a method for preparing the above-mentioned high-voltage resistant sodium ion battery positive electrode material, comprising the following steps:

[0014] Step 1: ball milling and mixing the sodium source, nickel iron manganese precursor, calcium source, aluminum source and magnesium source;

[0015] Step 2: aerobic calcination of the ball-milled mixture;

[0016] Step 3: Mix the product after aerobic calcination and the raw materials for the coating layer and aerobically calcine them.

[0017] In the above preparation method, the atmosphere of the aerobic calcination in step 2 is an air atmosphere or an oxygen atmosphere; the calcination temperature is 800-950° C., and the calcination time is 10-20 h.

[0018] In the above preparation method, the atmosphere of the aerobic calcination in step 3 is an air atmosphere or an oxygen atmosphere; the calcination temperature is 500-750° C., and the calcination time is 4-10 h.

[0019] In the above-mentioned preparation method, the raw materials used for the coating layer are La2O3, H3BO3, AF m。

[0020] In the above preparation method, the mixing method of the raw materials in step 3 is dry mixing or wet mixing.

[0021] In the above-mentioned preparation method, the wet mixing method is: dispersing the product after aerobic calcination and the raw materials for the coating layer in water or an organic solvent, stirring and heating until the water or the organic solvent is completely volatilized.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention is to treat the alkali metal layer with Ca 2+ Doping reinforcement, Al 3+ Doping reinforcement, then, using Mg 2+ Increase material conductivity and reduce Al doping 3+ The polarization brought about is finally carried out on the material by in-situ coating. The coating material contains borate and La elements, which on the one hand isolate the corrosion of the material by the electrolyte, thereby improving the material's ability to withstand high voltage. On the other hand, the high-strength boron-oxygen bond of borate is used for shallow doping to improve the stability of the surface layer. The high-strength bond energy of La element is used to maintain the stability of the coating layer structure, thereby ultimately achieving the stability of the core layer material, the coating material, and the interface between the core layer material and the coating material, especially the significant improvement of the surface stability of the doped core layer, thereby improving the capacity and cycle performance under high voltage conditions.

[0024] The core innovations of the present invention are:

[0025] 1. Through Ca 2+ 、Al 3+ Mg 2+ Doping strengthens the transition metal layer and reduces the polarization of the core layer, thereby improving the stability of the positive electrode material under high voltage conditions;

[0026] 2. Through coating, the corrosion of electrolyte to materials is isolated and the stability of materials is improved;

[0027] 3. By selecting borate anions to coat the core layer, a small amount of boron ions are doped in the shallow surface of the core layer, so that the adhesion of the coating layer is more firm and reliable, and the stability of the surface layer under high voltage is improved, so that the stability of the surface layer and the inner layer of the core layer is similar, and the stability during the cycle is improved;

[0028] 4. The La element is used as the main framework of the coating layer to improve the conductivity of the coating layer. La has high-strength bond energy and maintains the structural stability of the coating layer.

[0029] 5. Mg needs special control 2+ The dosage of this element, when used too much or too little, will affect the stability of the core layer. The reason is that: if there are too few magnesium ions, the polarization of the material cannot be improved, and the cycle decay during the charge and discharge process is accelerated; too much will cause the material to lack sodium, resulting in a decrease in the material capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a scanning electron microscope image of Example 1;

[0031] Figure 2 is a scanning electron microscope image of Example 2;

[0032] Figure 3 This is the cycle performance curve diagram of Example 9. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] Step 1: Add 0.48 mol Na2CO3, 1 mol nickel-iron-manganese precursor, 0.02 mol CaCO3, 0.05 mol Al2O3, and 0.0092 mol MgCO3 into a mixing tank for ball milling. After the ball milling is completed, take out the raw materials and put them in a sagger;

[0036] Step 2: Place the sagger filled with raw materials into a muffle furnace for sintering. In an air atmosphere, heat the temperature to 900°C at 5°C / min, and then keep the temperature constant for 15 hours to obtain the positive electrode material NFM. The chemical formula of the positive electrode material NFM is:

[0037] Na x Ca y (NiFeMn) 0.33x(1-z-e) Al zMg e O2;

[0038] Among them, x=0.96; y=0.02; z=0.1; e=0.0092;

[0039] Step 3: crush and sieve the sintered positive electrode material NFM, then add the positive electrode material NFM, La2O3 and H3BO3 into the mixing tank and mix them evenly. Put the mixed raw materials into the muffle furnace, heat the air (or oxygen) to 650℃ at 5℃ / min, and keep the constant temperature for 8h. After sintering, crush and sieve the raw materials to obtain the coated positive electrode material NFM-NLAO.

[0040] Among them, the mass ratio of NFM to La2O3 and H3BO3 is 1000:8, and the molar ratio of La2O3 and H3BO3 is 1:3.

[0041] The product of Example 1 of the present invention was observed by scanning electron microscope. Figure 1 shown.

[0042] Example 2

[0043] Step 1: Add 0.48 mol Na2CO3, 1 mol nickel-iron-manganese precursor, 0.02 mol CaCO3, 0.05 mol Al2O3, and 0.0092 mol MgCO3 into a mixing tank for ball milling. After the ball milling is completed, take out the raw materials and put them in a sagger;

[0044] Step 2: Place the sagger filled with raw materials into a muffle furnace for sintering. In an air (or oxygen) atmosphere, heat up to 800°C at 2°C / min, and then keep the temperature constant for 20 h to obtain the positive electrode material NFM.

[0045] Step 3: Crush and sieve the sintered positive electrode material NFM, then add the positive electrode material NFM, La2O3 and H3BO3 into a beaker filled with water, heat the oil bath to 90°C, stir and mix at 500 rpm until the solution is completely evaporated, put the evenly mixed raw materials into a muffle furnace, heat the air atmosphere to 500°C at 2°C / min, and maintain the constant temperature for 10 hours. After sintering, crush and sieve the raw materials to obtain the coated positive electrode material NFM-NLAO.

[0046] Among them, the mass ratio of NFM to La2O3 and H3BO3 is 1000:10, and the molar ratio of La2O3 and H3BO3 is 1:3.

[0047] The product of Example 2 of the present invention was observed by scanning electron microscope. Figure 2 shown.

[0048] Example 3

[0049] It is substantially the same as Example 2, except that the mass ratio of NFM to La2O3 and H3BO3 is 1000:20.

[0050] Example 4

[0051] The same as Example 1, except that the raw materials for preparing the positive electrode material NFM are as follows:

[0052] Na2CO3: 0.485mol;

[0053] NiFeMn precursor: 1 mol;

[0054] CaCO3: 0.01 mol;

[0055] Al2O3: 0.005mol;

[0056] MgCO3: 0.0023 mol;

[0057] The chemical formula of the positive electrode material NFM formed is: Na x Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2 ;

[0058] Among them, x=0.97; y=0.01; z=0.01; e=0.0023.

[0059] Example 5

[0060] The same as Example 1, except that the raw materials for preparing the positive electrode material NFM are as follows:

[0061] Na2CO3: 0.47 mol;

[0062] NiFeMn precursor: 1 mol;

[0063] CaCO3: 0.05 mol;

[0064] Al2O3: 0.05mol;

[0065] MgCO3: 0.023 mol;

[0066] The chemical formula of the positive electrode material NFM formed is: Na x Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2;

[0067] Among them, x=0.94; y=0.05; z=0.1; e=0.023.

[0068] Example 6

[0069] The same as Example 1, except that the raw materials of the coating material are La2O3, H3BO3, and MgF2;

[0070] The molar ratio of La2O3, H3BO3 and MgF2 is 1:3:0.02.

[0071] Example 7

[0072] The same as Example 1, except that the raw materials of the coating material are La2O3, H3BO3, and MgF2;

[0073] The molar ratio of La2O3, H3BO3 and MgF2 is 1:3:0.05.

[0074] Example 8

[0075] The same as Example 1, except that the raw materials of the coating material are La2O3, H3BO3, and AlF3;

[0076] The molar ratio of La2O3, H3BO3 and AlF3 is 1:3:0.02.

[0077] Example 9

[0078] The same as Example 1, except that the raw materials of the coating material are La2O3, H3BO3, AlF3, and MgF2;

[0079] The molar ratio of La2O3, H3BO3, MgF2 and AlF3 is 1:3:0.025:0.025.

[0080] Comparative Example 1

[0081] The same as Example 1, except that the amount of each raw material in step 1 is:

[0082] Na2CO3: 0.48 mol;

[0083] NiFeMn precursor: 1 mol;

[0084] CaCO3: 0.02 mol;

[0085] Al2O3: 0.05mol;

[0086] MgCO3: 0.03 mol;

[0087] The chemical formula of the positive electrode material NFM formed is: Nax Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2;

[0088] Among them, x=0.96; y=0.02; z=0.1; e=0.03.

[0089] Comparative Example 2

[0090] The same as Example 1, except that the amount of each raw material in step 1 is:

[0091] Na2CO3: 0.468 mol;

[0092] NiFeMn precursor: 1 mol;

[0093] CaCO3: 0.02 mol;

[0094] Al2O3: 0.05mol;

[0095] MgCO3: 0.002 mol;

[0096] The chemical formula of the positive electrode material NFM formed is: Na x Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2;

[0097] Among them, x=0.96; y=0.02; z=0.1; e=0.002.

[0098] Comparative Example 3

[0099] The same as Example 1, except that the amount of each raw material in step 1 is:

[0100] Na2CO3: 0.48 mol;

[0101] NiFeMn precursor: 1 mol;

[0102] CaCO3: 0.02 mol;

[0103] Al2O3: 0.04mol;

[0104] MgCO3: 0.0092 mol;

[0105] AlF3: 0.02 mol;

[0106] The chemical formula of the positive electrode material NFM formed is: Na x Cay (NiFeMn) 0.33x(1-z-e) Al z Mg e O (2-c) F c ;

[0107] Among them, x=0.96; y=0.02; z=0.08; e=0.0092; c=0.02.

[0108] Comparative Example 4

[0109] It is basically the same as Example 1, except that the coating material is Na3La2(PO4)3; correspondingly, boric acid is replaced by phosphoric acid.

[0110] Comparative Example 5

[0111] The method is substantially the same as Example 1, except that the La2O3 used in the coating layer is replaced by Al2O3 in equal moles.

[0112] Comparative Example 6

[0113] The method is substantially the same as Example 1, except that the La2O3 used in the coating layer is replaced by ZrO2 in equal moles.

[0114] Performance Testing

[0115] Test items include: 0.1C charge gram capacity, 0.1C discharge gram capacity, 1C discharge gram capacity, 50 weeks 1C cycle;

[0116] The test method for 0.1C charging gram capacity is: electrochemical test cabinet, constant current and constant voltage charging at 0.1C rate, nominal specific capacity is 170mAh / g;

[0117] The test method for 0.1C discharge gram capacity is: electrochemical test cabinet, constant current discharge at 0.1C rate, nominal specific capacity is 170mAh / g;

[0118] The test method for 1C discharge gram capacity is: electrochemical test cabinet, constant current discharge at 1C rate, nominal specific capacity is 170mAh / g;

[0119] The test method for 50 cycles of 1C is: electrochemical test cabinet, constant current and constant voltage charge and discharge cycle at 1C rate for 50 cycles, the nominal specific capacity is 170mAh / g. Figure 3 The relationship between the number of cycles and the discharge specific capacity of Example 9 is shown.

[0120] The test results are shown in Table 1 below;

[0121] Table 1 Test results

[0122] Voltage range 0.1C discharge capacity 0.1C discharge capacity 1C discharge capacity in grams 50 weeks 1C cycle Example 1 2.0-4.2V 198 177 156 92 Example 2 2.0-4.2V 196 177 157 90 Example 3 2.0-4.2V 197 175 155 92 Example 4 2.0-4.2V 196 178 157 91 Example 5 2.0-4.2V 194 176 157 92 Example 6 2.0-4.2V 197 177 159 93 Example 7 2.0-4.2V 196 176 161 94 Example 8 2.0-4.2V 192 171 154 97 Example 9 2.0-4.2V 197 176 160 96 Comparative Example 1 2.0-4.2V 195 174 153 88 Comparative Example 2 2.0-4.2V 197 174 150 81 Comparative Example 3 2.0-4.2V 192 170 149 91 Comparative Example 4 2.0-4.2V 193 173 152 86 Comparative Example 5 2.0-4.2V 188 168 147 80 Comparative Example 6 2.0-4.2V 194 174 155 83

[0123] Result analysis:

[0124] It can be seen from Examples 1 to 5 that the basic solution of the present invention can maintain a state with better comprehensive performance under high voltage conditions, indicating that the Ca, Al, Mg doping and borate and La element coating of the present invention are effective solutions for achieving capacity and cycle retention under high voltage conditions;

[0125] It can be seen from Example 1 and Example 2 that both dry and wet coating methods are applicable to the technical solution of the present invention, and there is no obvious performance difference between the two.

[0126] It can be seen from Examples 6 to 9 that the use of F, Al, and Mg in the coating layer can further supplement the shallow doping of the core layer, improve the shallow stability of the core layer, and improve the cycle stability. In terms of 1C discharge capacity per gram, there is a certain volatility compared to Example 1. Specifically, MgF2 has an advantage over AlF3 in 1C discharge capacity per gram, and AlF3 has an advantage over MgF2 in cycle performance. When the two are used together, they can achieve a dual improvement in discharge capacity per gram and cycle performance.

[0127] It can be seen from Comparative Example 1, Comparative Example 2 and Example 1 that the amount of Mg is a key factor and needs to be strictly controlled during the production process; it can be seen from the comparison between Comparative Example 3 and Example 8 that the effect of shallow doping after the coating layer is doped with F is much better than that of the bulk doping with F. It can be seen from the comparison between Comparative Example 3 and Example 1 that the performance of the bulk is still weakened to a certain extent after F doping;

[0128] It can be seen from Comparative Examples 4 to 6 that the selection of shell material is also a key aspect of performance improvement, which further proves the importance of the borate and La elements of the present invention for performance improvement.

[0129] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-voltage sodium-ion battery positive electrode material, characterized in that: It includes a core layer and a cladding layer; The chemical formula of the core layer is Na x Ca y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2; the chemical formula of the coating layer is Na3La2(BO3)3·(AF m ) n; 0.99≤x+2y≤1.04, 0.01≤y≤0.05, 0.01≤z≤0.1, 0<n≤0.05, 0.0023≤e≤0.023; A is Na, Mg and / or Al, m is the valence state of element A, and the weight of the coating layer is equivalent to 0.8-2% of the weight of the core layer.

2. A method for preparing a positive electrode material for a high-voltage sodium-ion battery according to claim 1, characterized in that: The steps include: Step 1: ball milling and mixing a sodium source, a nickel-iron-manganese precursor, a calcium source, an aluminum source, and a magnesium source; Step 2: aerobic calcination of the ball-milled mixture; Step 3: Mix the product after aerobic calcination and the raw materials for the coating layer and aerobically calcine them.

3. The preparation method according to claim 2, characterized in that: The atmosphere of the aerobic calcination in step 2 is an air atmosphere or an oxygen atmosphere; the calcination temperature is 800-950° C., and the calcination time is 10-20 h.

4. The preparation method according to claim 3, characterized in that: The atmosphere of the aerobic calcination in step 3 is an air atmosphere or an oxygen atmosphere; the calcination temperature is 500-750° C., and the calcination time is 4-10 h.

5. The preparation method according to claim 2, characterized in that: The raw materials used for the coating layer are La2O3, H3BO3, AF m .

6. The preparation method according to claim 2, characterized in that: The mixing method of the raw materials in step 3 is dry mixing or wet mixing.

7. The preparation method according to claim 6, characterized in that: The wet mixing method is: dispersing the product after oxygen calcination and the raw materials used for the coating layer into water or an organic solvent, stirring and heating until the water or the organic solvent is completely volatilized.

8. The preparation method according to claim 2, characterized in that: The steps include: Step 1: Add 0.48 mol Na2CO3, 1 mol nickel-iron-manganese precursor, 0.02 mol CaCO3, 0.05 mol Al2O3, and 0.0092 mol MgCO3 into a mixing tank for ball milling. After the ball milling is completed, take out the raw materials and put them in a sagger; Step 2: Place the sagger filled with raw materials into a muffle furnace for sintering. In an air atmosphere, heat the temperature to 900°C at 5°C / min, and then keep the temperature constant for 15 hours to obtain the positive electrode material NFM. The chemical formula of the positive electrode material NFM is: So x Approx y (NiFeMn) 0.33x(1-z-e) Al z Mg e O2 Among them, x=0.96; y=0.02; z=0.1; e=0.0092; Step 3: crush and sieve the sintered positive electrode material NFM, then add the positive electrode material NFM, La2O3, H3BO3, AlF3, and MgF2 into a mixing tank and mix them evenly. Put the mixed raw materials into a muffle furnace, heat the air to 650°C at 5°C / min, and keep the constant temperature for 8 hours. After sintering, crush and sieve the raw materials to obtain the coated positive electrode material NFM-NLAO. Among them, the mass ratio of NFM to La2O3 and H3BO3 is 1000:8, and the molar ratio of La2O3, H3BO3, MgF2 and AlF3 is 1:3:0.025:0.025.

Citation Information

Patent Citations

  • Sodium ion positive electrode material, preparation method thereof and sodium ion battery

    CN117219736A

  • Coated O3 type manganese-based sodium ion battery positive electrode material and preparation method thereof

    CN117638051A

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN118173762A